Positive psychology : the science of happiness and human strengths - Carr, Alan, 1957- (London ; New York : Routledge, 2011)
Remediating deficits and managing disabilities has been a central preoccupation for clinical psychologists. Positive Psychology, in contrast, is concerned with the enhancement of happiness and well-being, involving the scientific study of the role of personal strengths and positive social systems in the promotion of optimal wellbeing. Alan Carr's Positive Psychology has become essential reading for anyone requiring a thorough and accessible introduction to the field. This new edition retains all the features that made the first edition so popular, including: •accounts of major theories and relevant research •learning objectives •chapter summaries •research and personal development questions •suggestions for further reading •measures for use in research •glossaries of new terms. The book has also been completely updated to take account of recent research and major advances, and includes a new chapter on Positive Psychotherapy, an extended account of research on character strengths and virtues, and a discussion of recent ground-breaking research on emotional intelligence. This new edition of Positive Psychology will prove a valuable resource for psychology students and lecturers, as well as those involved in postgraduate training in related areas such as clinical psychology, social work, counselling and psychotherapy.
Happiness -- Positive traits -- Hope and optimism -- Flow -- Emotional intelligence -- Giftedness, creativity and wisdom -- Positive self -- Positive relationships -- Positive psychological therapy.
Includes bibliographical references and index.
Keywords: Geluk; Happiness; Positieve psychologie; Positive psychology